Effect of reinforcement of alkaline-treated sugar palm/bamboo/kenaf and fibreglass/ kevlar with polyester hybrid biocomposites: mechanical, morphological, and water absorption properties - Radzi, F.S.M.; Suriani, M.J.; Abu Bakar, A.; Khalina, A.; Ruzaidi, C.M.; Wan Nik, WB; Awang, M.; Zulkifli, F.; Abdullah, S.; Ilyas, R.A.; Eldin, Sayed M. (Elsevier, 2023)
In this age of globalisation, decreasing synthetic resources have exhilarated global communities to apply natural fibres as substitute materials for green technology development. The growth of products from lignocellulose fibre-reinforced composites has been a wide topic among material scientists and engineers due to their abundance, sustainability in nature, biodegradability, and availability at low cost. A series of natural/synthetic hybrid fibre-reinforced composites are prepared by reinforcing polyester resin as the matrix. Natural fibres such as sugar palm/kenaf/bamboo with fibreglass/Kevlar hybrid composite materials were used in this research to determine the mechanical and water absorption properties. The difference between the weight content of natural fibres which were 0 (control sample), 15, 45, and 60 wt% influenced their strength of mechanical properties. The Charpy impact and tensile test were performed following the ASTM D6110-10 and ASTM D3039, respectively. A water absorption test in accordance with ASTM D570-98 was also performed on three different natural fibre-reinforced hybrid composite materials to determine which composite had the best water resistance property. The results showed that hybrid fibre-reinforced composite for 45 wt% kenaf fibre possessed better tensile properties and 60 wt % sugar palm fibre performed better during the Charpy impact strength test compared to other natural/synthetic hybrid fibre-reinforced composites. It was concluded that sugar palm fibres demonstrated the best water resistance in this study.